Farmer perceptions on climate change and variability in semi-arid Zimbabwe in relation to climatology evidence - Moyo M; Mvumi BM; Kunzekweguta, M.; Mazvimavi K; Craufurd, Peter Q.; Dorward, P. (African Crop Science Society, 2012)
Farmers in semi-arid Zimbabwe prioritise climate variability as their major agricultural productivity-reducing problem. This paper raises the importance of considering local farmers perceptions on climate risk, as this greatly influences on-farm investments and decision-making in agricultural management and production in semiarid Zimbabwe. A study was conducted in two districts of semi-arid Zimbabwe using participatory research techniques, to investigate farmers perceptions of climate variability and whether these perceptions correspond with historical climatic data. The study showed that farmers perceived climatic and weather patterns to have changed over the past decade or two, as indicated by erratic rainfall patterns, decreased rainfall and temperature increases, leading to crop productivity decline and increased livestock morbidity and mortality. Majority of respondents (75%; n=81) were highly risk-averse, perceiving that most of the seasons in any ten given years could be poor. The climatic data show no evidence that corroborates the farmers perceptions, with only temperature showing a clear signal, indicating the influence of other non-climatic factors. The climate data show rainfall variability to be a normal characteristic of the study sites, with deviations from the climatic rainfall means (or the poor seasons) being cyclical and occurring once in every three seasons over the past 40 years. The study highlights strategies that farmers could implement to enhance agricultural productivity in the semi-arid areas to adapt to climate change and variability.